Selection of Non-Restorable Reserved Energy Process Control and Management Systems - V. A. Anischenko; A. N. Ivanova; Е. L. Myslo (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2012)
The paper considers problems pertaining to selection of non-restorable continuously reserved discrete control and management systems of electric and heat and power processes. Two problems concerning system optimization on the basis of the following criteria – their reliability and cost have been solved in the paper.